ANALISIS PENDAPATAN USAHA TERNAK AYAM PETELUR DI DESA TEGALHARJO KECAMATAN TRANGKIL KABUPATEN PATI - Eko Budi Cahyono; Eko Suharyono; Ryantoko Setyo Prayitno (Universitas Islam Malang, 2020)
The livestock sector is expected to make a real contribution to the development of the nation's economy. Livestock development is also directed at increasing the quality of production, increasing income, expanding employment opportunities and providing business opportunities for people in rural areas. Layer are one of the poultry commodities that have an important role as egg producers to support the availability of cheap and easy to obtain animal protein. The population of layer in Pati Regency in 2018 was 265,020 birds (BPS, 2020). Layer are increasingly in demand in the village of Tegalharjo as a profitable poultry business opportunity. Many breeders choose the business of layer as a side business or as their main income. The objectives of this study are 1). To determine the business income of layer, 2) To determine the business feasibility of layer, 3) To determine the effect of pullets, feed costs, medicines and labor on the income of layer. The research material was in the form of layer in Tegalharjo Village, Trangkil District, Pati Regency. Data collection for 3 months (March - May). The results of the research on layer in the village of Tegalharjo are feasible to work with an income of IDR 11,784,946.17 / ST / period and simultaneously there is an effect of the cost of pullets (X1), feed (X2), medicines (X3) and labor ( X4) to income.